Information Security and Privacy Rights of Social Media Users Survey on Meta Platforms - Hamad Ameen, Marewan Q.; Hwaez , Salar D. (Mitanni Journal of Humanitarian Sciences, 2024)
Social media has positively impacted our lives as well as being a benefit of modern lifestyle it is mostly used for entertaining, information sharing, news, and learning. Users did not really give their information's security to social media much consideration when using it. In this paper that is based on a survey, researchers have tried to analyze how well users understand social media information security and privacy. Our assessment indicates there is still a need for social media users to be informed more about information security options that are accessible. Keywords: Social media, information security, Privacy Rights Meta Platforms